2015
DOI: 10.1080/14613808.2015.1108299
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of the impact on students of the Musical Futures approach

Abstract: Music education has faced considerable challenges in trying to bridge the gap between music in young people's lives and that taking place in the classroom. The 'Musical Futures' initiative aimed to devise new and imaginative ways of engaging young people, aged 11-19, in music activities through a process of informal learning based on popular music. This research aimed to explore teachers' perceptions of the impact of adopting the Musical Futures approach on students' learning and attainment. Twenty-eight music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 11 publications
(14 reference statements)
3
43
0
2
Order By: Relevance
“…Along with its success, Musical Futures has faced significant challenges in its short existence. A study conducted by Hallam, Creech, and McQueen (2011) found that some music teachers feared losing control of the classroom through a Musical Futures approach. Additionally, some felt that their traditional musical training at times put them at a disadvantage to guide students in popular genres (Armon-Anderson & Lemar-Denson, 2015; Baker, 2012).…”
Section: Literature Review: Popular Music Pedagogiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Along with its success, Musical Futures has faced significant challenges in its short existence. A study conducted by Hallam, Creech, and McQueen (2011) found that some music teachers feared losing control of the classroom through a Musical Futures approach. Additionally, some felt that their traditional musical training at times put them at a disadvantage to guide students in popular genres (Armon-Anderson & Lemar-Denson, 2015; Baker, 2012).…”
Section: Literature Review: Popular Music Pedagogiesmentioning
confidence: 99%
“…Furthermore, educators shared that students working in groups autonomously sometimes lost focus, that it was difficult balancing the support of student autonomy and their need for help, that lack of access to instruments could impede the instrumental development of students, and that it was challenging to instill practicing routines other than “repetitive” and “traditional” ones. In addition to the problems raised in the Hallam et al (2011) survey, friction can occur from adopting informal music learning practices within the bureaucratic functioning of a school, considering that informal music learning can impede the achievement of broader curricular goals as well as contradict the educational philosophy of music teachers (D’Amore & Smith, 2017; Green, 2014). Moreover, adopting the Musical Futures approach generates the risk of students disregarding their teacher’s competencies (Pitts, 2011).…”
Section: Literature Review: Popular Music Pedagogiesmentioning
confidence: 99%
See 3 more Smart Citations